-75=-10f-3(2f+9)

Simple and best practice solution for -75=-10f-3(2f+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -75=-10f-3(2f+9) equation:


Simplifying
-75 = -10f + -3(2f + 9)

Reorder the terms:
-75 = -10f + -3(9 + 2f)
-75 = -10f + (9 * -3 + 2f * -3)
-75 = -10f + (-27 + -6f)

Reorder the terms:
-75 = -27 + -10f + -6f

Combine like terms: -10f + -6f = -16f
-75 = -27 + -16f

Solving
-75 = -27 + -16f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '16f' to each side of the equation.
-75 + 16f = -27 + -16f + 16f

Combine like terms: -16f + 16f = 0
-75 + 16f = -27 + 0
-75 + 16f = -27

Add '75' to each side of the equation.
-75 + 75 + 16f = -27 + 75

Combine like terms: -75 + 75 = 0
0 + 16f = -27 + 75
16f = -27 + 75

Combine like terms: -27 + 75 = 48
16f = 48

Divide each side by '16'.
f = 3

Simplifying
f = 3

See similar equations:

| 5(6+6k)=30+k | | 24b+8= | | -7-7(7p+1)=29-6p | | 7x-x^2=0 | | 5x+4y=122 | | 7x-12x=32 | | 8(t-6)+6t=7(2t+5)-11 | | 5n-4=-74 | | 19x+17=19x-17 | | 12t-(7-3t)=-8(-2x+6)-7 | | 5-2(x+8)=30 | | 5y-15=3(2y)-21 | | 16u^2-u^2w^4=0 | | 2n=84 | | -7x+8=-97 | | 3x^2+5x-100=0 | | 54-2x=180 | | c=535+4.50n | | -9x+-13x+7= | | 4x^2+12.5x-15=0 | | 3x-4+2x-8=4x+3-7x | | 13x-19y=-23 | | .5r+2(.75r-1)=.25+6 | | 2x^2+6.25x-7.5=0 | | 5+10r-2=5r+11-3r | | 4(x+2)=4(x+7) | | 0.9(x+80)+0.5x=121 | | 3(2p+7)=15(p+4) | | 0.32(6)+0.08x=0.16(30+x) | | (13a+7)(6a-7)=0 | | 3(p+7)=15(p+4) | | 2(2x+5)+2(3x)=110 |

Equations solver categories